Observing the Volcano World Volcano Crisis Communication (Advances in Volcanology,, 2018)
This book provides a comprehensive overview of volcanic crisis research, the goal being to establish ways of successfully applying volcanology in practice and to identify areas that need to be addressed for future progress. It shows how volcano crises are managed in practice, and helps to establish best practices. Consequently the book brings together authors from all over the globe who work with volcanoes, ranging from observatory volcanologists, disaster practitioners and government officials to NGO-based and government practitioners to address three key aspects of volcanic crises. First, the book explores the unique nature of volcanic hazards, which makes them a particularly challenging threat to forecast and manage, due in part to their varying spatial and temporal characteristics. Second, it presents lessons learned on how to best manage volcanic events based on a number of crises that have shaped our understanding of volcanic hazards and crises management. Third, it discusses the diverse and wide-ranging aspects of communication involved in crises, which merge old practices and new technologies to accommodate an increasingly challenging and globalised world. The information and insights presented here are essential to tapping established knowledge, moving towards more robust volcanic crises management, and understanding how the volcanic world is perceived from a range of standpoints and contexts around the globe.